ANALISIS PENGARUH PERSPEKTIF FRAUD PENTAGON TERHADAP FRAUDULENT FINANCIAL REPORTING (Studi Kasus pada Perusahaan BUMN yang Terdaftar di BEI Periode 2014- 2018) - Alvin, Sofiana; Widarno, Bambang; Kristianto, Djoko (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2020)
The theme of this research is frauduluent financial reporting. The purposeof this study is to identify indication fraudulent financial reporting using thePentagon fraud theory. Pentagon fraud theory has five elements of fraud riskthese are pressure, opportunity, rationalization, competence, and arrogance.Testing of the pentagon fraud risk elements uses proxy variables, namely financialstability, external pressure, ineffective monitoring, nature of industry, change inauditor, change in director, and Number of CEO’s Pictures. Meanwhile, for thefraudulent financial reporting variable using proxy F-Score. The sample used was16 state-owned companies listed on the Indonesia Stock Exchange in the period2014-2018 with by means of a method of sampling the sampling method ofpurposif. An instrument of analysis that was used in this research was multiplelinier regression analysis. The results of the study obtained the conclusion thatthere are two variables which were significant negative in influencing thefinancial statement fraud, these are external pressure and nature of industry.Meanwhile financial stability, ineffective monitoring, change in auditors, changein directors and number of ceo’s picture has not been affecting in fraudulentfinancial reporting.